NMD-degradome sequencing reveals ribosome-bound intermediates with 3′-end non-templated nucleotides - Kurosaki, Tatsuaki; Miyoshi, Keita; Myers, Jason R.; Maquat, Lynne E. (Nature structural & molecular biology, 2018)
Nonsense-mediated messenger RNA decay (NMD) controls mRNA quality and degrades physiologic mRNAs to fine-tune gene expression in changing developmental or environmental milieus. NMD requires that its targets are removed from the translating pool of mRNAs. Since the decay steps of mammalian NMD remain unknown, we developed assays to isolate and sequence direct NMD decay intermediates transcriptome-wide based on their co-immunoprecipitation with phosphorylated UPF1, which is the active form of this essential NMD factor. We show that, unlike steady-state UPF1, phosphorylated UPF1 binds predominantly deadenylated mRNA decay intermediates and activates NMD cooperatively from 5′- and 3′-ends. We leverage method modifications to characterize the 3′-ends of NMD decay intermediates, show that they are ribosome-bound, and reveal that some are subject to the addition of non-templated nucleotide. Uridines are added by TUT4 and TUT7 terminal uridylyl transferases and removed by the Perlman syndrome-associated exonuclease DIS3L2. The addition of other non-templated nucleotides appears to inhibit decay. Newly developed assays to isolate and sequence direct NMD decay intermediates show that these are ribosome bound and can be subject to the addition of non-templated nucleotides, which affects their decay.